Monitoring of Ecosystem Services for Water Regulation in the Central and Upper Cisangkuy Watersheds - Hidiya, Miesriany; Giofandi, Eggy Arya; Tunggadewi, Andini Tribuana; Ratnawati, Beata; Tjahjono, Boedi (Jurnal Ilmu Tanah dan Lingkungan, 2025)
Water regulation ecosystem services in the middle and upper parts of the Cisangkuy watershed play a vital role in the lives of humans and other living beings in the downstream areas. This is related to daily water needs as well as the threat of disasters, given that ecosystem damage in the upstream areas can lead to floods, as has frequently occurred in the research area. This study aims to monitor water regulation ecosystem services based on the biophysical characteristics of the region. The approach used is based on Multi Criteria Evaluation of three main parameters: Topographic Wetness Index, Normalized Difference Vegetation Index, and Slope Gradient. The main data used were 30m SRTM DEM and Landsat 5 TM and 8/9 OLI-TIRS satellite imagery for the period 2000–2024. The results of the study show that the TWI values of the research area are spatially dominated by “high” (40.72%) and “very high” (36.79%) classes. For the slope classes, they are dominated by “moderately steep” (23.09%) and “steep” (23.07%) classes. Meanwhile, for vegetation density (NDVI), there was a dynamic change in area. The “very dense” class experienced a significant increase in area from 0.43% (2000) to 1.19% (2004), and sharply increased to 45.26% (2024). Meanwhile, the “dense” class briefly rose from 30.53% (2000) to 38.58% (2004), but then decreased to 26.16% (2024). For the “medium” density class, it briefly rose from 45.05% (2000) to 47.43% (2004) but then decreased to 18.47% (2024). This dynamic change in area impacted the value of water regulating ecosystem services, where the “high” class initially decreased from 37.95% (2000) to 17.23% (2004), but then increased again to 37.76% (2024). These findings confirm that there has been an improvement in the ecosystem of the upper and middle Cisangkuy Watershed over a 20-year period (2004 to 2024). This ecosystem condition is expected to be maintained or further improved to effectively reduce the incidence of floods and their impacts in downstream areas in the future.